Production of human pro-relaxin H2 in the yeast Pichia pastoris. Issue 1 (December 2017) - Cimini, D.; Corte, K.; Finamore, R.; Andreozzi, L.; Stellavato, A.; Pirozzi, A.; Ferrara, F.; Formisano, R.; De Rosa, M.; Chino, M.; Lista, L.; Lombardi, A.; et al.
Abstract Background Initially known as the reproductive hormone, relaxin was shown to possess other therapeutically useful properties that include extracellular matrix remodeling, anti-inflammatory, anti-ischemic and angiogenic effects. All these findings make relaxin a potential drug for diverse medical applications. Its precursor, pro-relaxin, is an 18 kDa protein, that shows activity inin vitro assays. Since extraction of relaxin from animal tissues raises several issues, prokaryotes and eukaryotes were both used as expression systems for recombinant relaxin production. Most productive results were obtained when usingEscherichia coli as a host for human relaxin expression. However, in such host, relaxin precipitated in the form of inclusion bodies and, therefore, required several expensive recovery steps as cell lysis, refolding and reduction. Results To overcome the issues related to prokaryotic expression here we report the production and purification of secreted human pro-relaxin H2 by using the methylotrophic yeastPichia pastoris as expression host. The methanol inducible promoter AOX1 was used to drive expression of the native and histidine tagged forms of pro-relaxin H2 in dual phase fed-batch experiments on the 22 L scale. Both protein forms presented the correct structure, as determined by mass spectrometry and western blotting analyses, and demonstrated to be biologically active in immune enzymatic assays. The presence of the tag allowed to simplify pro-relaxin purification obtaining higher purity. Conclusions This work presents a strategy for microbial production of recombinant human pro-relaxin H2 inPichia pastoris that allowed the obtainment of biologically active pro-hormone, with a final concentration in the fermentation broth ranging between 10 and 14 mg/L of product, as determined by densitometric analyses.